Upacara Penghormatan Jenazah dalam Adat Kematian Dayak Aoheng dan Liturgi Kematian Gereja Katolik - Berahang, Mikael (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2023)
This study aims to explore and describe of ceremonies honouring the dead person in the adat of the Dayak Aoheng, that can be practiced in the Light of the Catholic Faith as efforts to adapt a series of ceremonies honouring the dead person. The research was conducted among the Dayak Aoheng of the Semukung sub-group, who live in Long Apari and Noha Silat Villages, Long Apari District, Mahakam Ulu Regency, East Kalimantan. This study uses a comparative qualitative method with interview data collection techniques and related document collection. The informants in this study were fifteen informants spread over two research sites. The results of the study reveal that there are several parts of the series of ceremonies honouring the dead person in the adat of the Dayak Aoheng that can be proposed for adaptation into the Liturgy of Death of the Catholic Church to enrich the Church's Liturgy and the local cultural wisdom. The series of ceremonies honouring the corpse that can be proposed for adaptation efforts are found in the series of ceremonies undertaken before the death and at the time of death, during the taking care of and caring for the corpse, during the praying for the corpse and consoling the family, and in the funeral ceremonies.